Effect of vitamin C supplementation on haematological and serum biochemical indices of laying hens diagnosed with fowl typhoid under tropical environment - Opoola, E.; Atte, P.I.; Makinde, O.J.; Aganbi, B. (Nigerian Journal of Animal Science, 2023)
To evaluate the effect of four different levels of vitamin C supplementation on the haematological and serum biochemical parameters of laying hens infected with fowl typhoid, a trial was conducted with 300 Isa Brown layer hens. The experiment was conducted by using a completely randomized design with 5 treatments, 3 replicates, and 20 hens in each replicate. Treatments included basal diet (control) and basal diet plus 100, 150, 200, and 250 mg of vitamin C/kg of diet, respectively. At the end of the 12-week treatment period, samples of blood were collected to determine haematological and serum biochemical values. The results showed that white blood cells (WBC), mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH), and mean corpuscular haemoglobin concentration (MCHC), uric acid and cholesterol were significantly (p<0.05) higher in layer hens fed vitamin C than those fed the control diet. However, Packed cell volume (PCV), haemoglobin count (HC), red blood cell (RBC), urea, creatinine, glucose, alkaline Phosphatase (ALP), albumin, total protein and serum vitamin C were not significantly (p>0.05) affected by dietary treatments. These results indicated that the inclusion of vitamin C at the level of 150mg/kg of diet may have a positive effect on immunity of laying hens.